Industrial biotransformations (Wiley-VCH, 2006)
The book gives information on industrial biotransformation - an industrial importance. The book is divided into 7 sections: History of industrial biotransformations - dreams and realities; The enzyme classification; Retrosynthetic Biocatalysis; Optimization of industrial enzymes by molecular engineering; basics of bioreaction engineering; processes; quantitative analysis of industrial biotransformation